Prediction and classification of expansive clay soils - Agus Setyo Muntohar (Taylor & Francis Grup, 2006)
This chapter deals with the prediction and classification of the degree of expansiveness of clay soil. Statistics analysis was introduced as a simple technique for identifying and predicting the degree of swelling. There were three properties which were most strongly correlated to swelling potential (i.e. plasticity index, liquid limit, and clay fraction). In general, the models in the current study showed good correlation compared with previous models cited in the literature. The multiple linear regression model gave the best-fit for all soil conditions.